I'm pretty sure that the answer is 71, hope it helped!
Answer:
no, because for x=-3, y would have to be -31
Step-by-step explanation:
boy oh boy (or girl oh girl) - you wrote this in a horrible, horrible format.
I can only guess what your problem and the fitting answer would be.
y = -2×x^2 + 3×x - 4
-4 = -2×(-3)^2 + 3×(-3) - 4
-4 = -2×9 - 9 - 4
-4 = -18 - 9 - 4
-4 = -31
and that is wrong. for (-3,-4) to be on the graph of the function, y would have to be -4 when using x=-3 in the function. but y = -31 for x= -3.
Answer:
Median = 6.5 or 6 1/2
HOPE THIS HELPED! HAVE A GREAT DAY! :)
Answer:
(x - 2)(x + 1)(2x -1)
Step-by-step explanation:
We use synthetic division as a tool for factoring the given expression. The coefficients of the terms given are {2, -3, -3, 2}. If x - 2 is a factor of this expression, then 2 is a root. We perform synthetic division as follows:
2 / 2 -3 -3 2
4 2 -2
-------------------------------
2 1 -1 0
Next, we determine whether or not (2x - 1)(x + 1) represents the remaining factor(s). Using -1 as divisor, we get:
-1 / 2 1 -1
-2 1
---------------------
2 -1 0
Since the remainder is zero, x + 1 must be a factor and (2x - 1) the third factor. Answer D is correct.